ANALISIS BRAND AWARENESS, BRAND ASSOCIATION PERCEIVED QUALITY DAN PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN - AYU HARTININGTIYA; Mochamad Assegaff (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2010)
As for intention of this research is to analyses influence of awareness brand to decision ofpurchasing of motorbike of Honda in Kecamatan Kaliwungu Kabupaten Kendal, to analyseinfluence of assosiation brand to decision of purchasing of motorbike of Honda to analyseinfluence of perceived of quality to decision of purchasing of motorbike of Honda and toanalyses influence of awareness brand, assosiation brand and perceived of quality todecision of purchasing of motorbike of Honda. In this research of population which in usingis all user of motorbike parrot brand of Honda exist. Amount of taken sample will be roundedup to become 100 responder with its intake method of him is the non sampling probality.Data analyzer which is used in this research is validity test, test reliability, analyses doubledregression, examination of coefficient and hypothesis of determination. Pursuant to result ofanalysis hence can be concluded as follows there are influence which is significant betweenawareness brand to Decision of purchasing, there are influence which is significant amongassociation brand to Decision of purchasing, there are influence which is significant amongperceived of quality to decision of purchasing, there are influence which is significant amongawareness brand ( X1), association brand ( X2) and perceived of quality ( X3) to decision ofpurchasing ( Y) and Coefficient value of determination ( Adjusted R Square) is equal to 0,596or 59,6% meaning variable constribution of brand awareness ( X1), association brand ( X2)and perceived of quality ( X3) to Decision of purchasing ( Y) equal to 77,6% and the rest40,4% influenced by other factors.Keyword : Brand Awareness, Brand Association, Perceived Quality, Decision of Purchasing